2015
DOI: 10.1002/jso.24125
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications and overall survival after pancreaticoduodenectomy for pancreatic ductal adenocarcinoma

Abstract: INTRODUCTION Pancreaticoduodenectomy (PD) performed for pancreatic ductal adenocarcinoma (PDA) has a postoperative morbidity of 40–50%. In this study, we analyzed the impact of high grade complications after PD for PDA on overall survival. METHODS 596 patients that underwent PD for PDA between 2001–2009 were identified from a prospective database. Complications were defined and graded (1–5) as per our Institutional Surgical Secondary Events Program. High grade complications were defined as ≥ grade 3. Postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
83
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 39 publications
10
83
0
1
Order By: Relevance
“…As expected, the overall R0 resection rates reported in our review (70–77 %) are slightly lower, as reported by two recent studies (84–92 %) on borderline resectable disease 24,25. Surgical outcomes post-resection seem comparable with outcomes in upfront resectable patients, although still based on immature data 2628…”
Section: Discussionsupporting
confidence: 82%
“…As expected, the overall R0 resection rates reported in our review (70–77 %) are slightly lower, as reported by two recent studies (84–92 %) on borderline resectable disease 24,25. Surgical outcomes post-resection seem comparable with outcomes in upfront resectable patients, although still based on immature data 2628…”
Section: Discussionsupporting
confidence: 82%
“…Although the mortality of PD is less than 5%, the morbidity is still approximately 40% [31]. RPD is expected to decrease these complications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, R1 status has a stronger association with survival time than IMP3 or Ki-67 expression. Recently, Kato et al 11 and other investigators found a signi cant association between prognosis and R0 versus R1 disease 21,22 ; however, a multi-institutional study conducted in Japan found no association 23 . Our ndings imply that GLUT-1 expression depends upon the microscopic existence of residual tumors, or R1 disease.…”
Section: Discussionmentioning
confidence: 93%